Aksara Jawa Sebagai Ide Dasar Perancangan Typeface Kampung Tembalangan. - Bernardus Satria Agasta Dwi Cahyono; Rakhmad Maulidi; Mahendra Wibawa (MAVIS : Jurnal Desain Komunikasi Visual, 2023)
Tembalangan is a densely populated urban settlement located on Bunga Kumis Kucing Street in the city of Malang, East Java. This vibrant community holds tremendous potential, ranging from its rich natural resources to its captivating historical and cultural heritage. The natural resource potential of Tembalangan is evident in its proximity to the Brantas River and the presence of three natural water sources that are still utilized by the local residents. Additionally, the village boasts a rich historical and cultural legacy, with traces of the ancient Hindu kingdom civilization. However, the passage of time has gradually eroded some of this potential. In response to these challenges, designers have been motivated to craft and enhance one aspect of the visual identity, with the ultimate goal of making Tembalangan more widely recognized and celebrated for the unique character that has flourished within its urban landscape.